(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
Universities (IES) use the Strategic Plan as a management tool. This article will try to integrate that principles and indicators as the variables to study that derive the research question: How do the strategic indicators influence the Planning Management of a Public University? As a main objective, it is intended to establish the contribution of strategic indicators in the development of quality operations to make a proposal that contributes to decision making of a university. To do this, opinions will be obtained from the main actors involved in the research problem; significant contributions will be defined for each mission axis; and, the most relevant indicators will be selected to establish a system of indicators that contributes to decision making. The applied approach was qualitative with a descriptive dimension and the interview was used for data collection. It is concluded that the strategic indicators have a significant impact on decision making within the Planning Management of a public institution of higher education, a technical perspective of the application of indicators aimed at quality is obtained and a baseline is established for the development of other studies.